2018
DOI: 10.1007/s13730-018-0327-0
|View full text |Cite
|
Sign up to set email alerts
|

Penile calciphylaxis in a patient on combined peritoneal dialysis and hemodialysis

Abstract: Calciphylaxis presents with painful purpura and intractable skin ulcers on the trunk and particularly the distal extremities, and it mainly occurs in patients on chronic dialysis. A 66-year-old man with renal failure due to diabetic nephropathy was on peritoneal dialysis alone for 1 year, followed by peritoneal dialysis combined with hemodialysis for 3 years. He developed calciphylaxis of the penis, which was diagnosed from the skin biopsy findings and clinical observation. To treat this condition, PD was stop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…On the other hand, relatively few case reports have described the effect of STS for calciphylaxis in Japanese patients [8][9][10][11][12][13] . STS was effective in all of the previously reported Japanese patients who were undergoing dialysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, relatively few case reports have described the effect of STS for calciphylaxis in Japanese patients [8][9][10][11][12][13] . STS was effective in all of the previously reported Japanese patients who were undergoing dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…STS was effective in all of the previously reported Japanese patients who were undergoing dialysis. In two case reports, STS (10 g/ day) was administered 3 times/week during dialysis 10,11) . Conversely, Tokashiki et al and Ishikawa et al administered 20 and 5-25 g/day, respectively 9,13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, less than 80 cases of penile calciphylaxis have been described in the literature but the prevalence of the pathology is probably underestimated. Penile calciphylaxis is an exclusion diagnosis that is based on the combination of clinical, biological, and histological elements 7 . Clinically, the patient presents with ulcered and painful lesions that are resistant to treatment and appear in the context of end‐stage kidney disease and often dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, deep biopsy can provide information that is useful for diagnosis. The von Kossa staining highlights calcium deposits, but their presence is not specific and could depend on the biopsy site and medical history of the patient 7 . However, a recent comparative study demonstrated that the presence of more or fewer interstitial vascular calcifications in hemodialyzed patients has good sensitivity and specificity for calciphylaxis and does not seem to be related to dialysis 8 .…”
Section: Discussionmentioning
confidence: 99%